Análise da utilização de uma ferramenta de fórum de discussão baseado em mapas conceituais: um experimento no sistema UAB-UFAL - Miranda, Sunny Kelma Oliveira (2017)
The process of teaching and learning online has been strengthened in recent years with a technological evolution that allows the student to participate in classes and carry out their activities anywhere and at any time. One of these common activities in a virtual learning environment is to interact in the Discussion Forum with the other students in the class. However, the discussion forums have presented a problem of little interaction between learners and more direct answers to the teacher-tutor of the class. How some possible causes for this undesired attitude of the students were identified: the formal use of the language, demanded in this environment, can inhibit the participation of the learners; difficulty in understanding the discussion by structuring nested messages. As a workaround to this type of forum, a dynamic tool structured by conceptual maps (called the bMC Forum) was conceived, where the learner discusses the proposed theme by identifying key concepts and relating them to new concepts arranged in the collaborative conceptual map. In this way, the objective of this work was to develop and analyze the use of this tool in the promotion of more direct, objective and meaningful interactions among apprentices, based on previous studies. For that, an experimental research with the use of the tool was delineated by a class of a graduation course of the Open University of Brazil in UFAL. Data were collected and analyzed qualitatively from the students' records in the experiment environment, observations of the interactions and questionnaires applied to the apprentices and the class teacher. As a general result, in the teacher’s view, the tool had a satisfactory performance of the students, performing good interactions argued for the construction of the conceptual map. And in the students' view, the tool was well evaluated, concluding that its use facilitated the reading and understanding of what was discussed, as well as helped to better assimilate the exposed content.